Determination of indoor 222Rn concentrations level on different room sizes in academic building at Universiti Malaysia Kelantan Jeli campus - Mohammad Khairul Azhar Abdul Razab; Nur Liyana Hamzah; Siti Fatimah Abd Karim; Nur Ezati Azhar; Nor Hakimin Abdullah; An'Amt bin Mohamed Noor; Mazlan Mohamed; Zulhisyam Abdul Kari @ Abdullah; Noraina Adam (Trans Tech Publications, 2017)
The objectives of this study are to briefly monitor the 222Rn concentration in selected study area and to investigate its correlation with the environmental factors (pressure, humidity and temperature). 222Rn concentrations were monitored in three different sizes of lecture rooms known as BK 6, BK 7 and BK 8 at academic building, Universiti Malaysia Kelantan (UMK) Jeli Campus. Radon monitor known as Sentinel 1030 has been used to collect 210 readings of 222Rn concentration data. Environmental factors for each study areas was analyzed by using Pearson correlation. The average 222Rn concentrations for BK 6, BK 7 and BK 8 were found at 0.29 pCi/L, 0.31 pCi/L and 0.72 pCi/L, respectively. BK 8 with 277.97 m³ obtained higher 222Rn concentrations than BK 6 with 440.98 m³, followed by BK 7 with 292.67 m³. From the results, 222Rn concentration in BK 6 and BK 7 are influenced by temperature and pressure, correspondingly. However, no correlation of environmental factors found in BK 8.